TNF-α induces VE-cadherin-dependent gap/JAIL cycling through an intermediate state essential for neutrophil transmigration - Kipcke, Jan Philip; Odenthal-Schnittler, Maria; Aldirawi, Mohammed; Franz, Jonas; Bojovic, Vesna; Seebach, Jochen; Schnittler, Hans (Frontiers in Immunology, 2025)
Inflammatory endothelial phenotypes describe distinct cellular patterns essential for controlling transendothelial migration of leukocytes (TEM). While TNF-α-induced CAM expression mediates leukocyte interaction, the role of a potential inflammatory morphological phenotype (IMP) – characterized by barrier-function decrease and shape-change in TEM – remains unclear. This study identifies the TNF-α-induced IMP as indispensable for neutrophil TEM, while regulating barrier-function. The TNF-α-induced IMP progresses through two states: an intermediate state that transiently enhances barrier function via MLC-dephosphorylation, junctional actin recruitment and VE-cadherin linearization, protecting the monolayer from collapse; while the subsequent development of the IMP requires MLC rephosphorylation, junctional actin disassembly, stress fiber formation and Arp2/3-mediated membrane protrusions causing shape-change. This in turn dilutes junctional VE-cadherin, forming intercellular gaps for neutrophil TEM, while inducing junction-associated intermittent lamellipodia (JAIL) to locally restore VE-cadherin adhesion, appearing as gap/JAIL cycles driving junctional dynamics. VE-cadherin overexpression blocks TNF-α-induced IMP and gap/JAIL cycling, reducing TEM by ~80% without altering CAM expression. These findings highlight gap/JAIL cycling and MLC phosphorylation as key IMP regulators and potential therapeutic targets for inflammatory diseases.